2015
DOI: 10.1182/blood-2015-02-626754
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of PD-L1/PD-1–mediated CD8 T-cell dysfunction in the context of aging-related immune defects in the Eµ-TCL1 CLL mouse model

Abstract: Key Points• PD-L1/PD-1-mediated CD8T-cell dysfunction develops with CLL in different organs, and similarities to agingrelated immune defects exist.• PD-1 1 normal T cells have markedly different effector functions than PD-1 1 CLL T cells.T-cell defects, immune suppression, and poor antitumor immune responses are hallmarks of chronic lymphocytic leukemia (CLL), and PD-1/PD-L1 inhibitory signaling has emerged as a major immunosuppressive mechanism. However, the effect of different microenvironments and the confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
89
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 55 publications
(70 reference statements)
5
89
0
1
Order By: Relevance
“…43,44 Moreover, tumor cells express immunosuppressive ligands like programmed death-ligand 1 (PD-L1) and PD-L2 that inhibit proliferation and activation of effector memory T cells. 41,45 In addition, the recruitment of tumor supporting innate myeloid cells; including nurselike cells, tolerogenic DCs, tumor-associated macrophages (M2-polarized) and MDSCs; to the tumor micro-environment occurs, which enhance the state of tolerance. 43,[46][47][48][49] Through these mechanisms, malignant B cells, besides inhibiting anti-tumor immunity, also impair immune responses that are crucial for the control of both common and opportunistic pathogens.…”
Section: Infections In Patients With Lymphoid Malignanciesmentioning
confidence: 99%
“…43,44 Moreover, tumor cells express immunosuppressive ligands like programmed death-ligand 1 (PD-L1) and PD-L2 that inhibit proliferation and activation of effector memory T cells. 41,45 In addition, the recruitment of tumor supporting innate myeloid cells; including nurselike cells, tolerogenic DCs, tumor-associated macrophages (M2-polarized) and MDSCs; to the tumor micro-environment occurs, which enhance the state of tolerance. 43,[46][47][48][49] Through these mechanisms, malignant B cells, besides inhibiting anti-tumor immunity, also impair immune responses that are crucial for the control of both common and opportunistic pathogens.…”
Section: Infections In Patients With Lymphoid Malignanciesmentioning
confidence: 99%
“…The Em-TCL1 model was selected because of its extensive prior characterization, including studies that demonstrated its utility in investigating tumor-induced immune defects. [50][51][52] Our results demonstrate that BRAF V600E accelerates Em-TCL1 B-cell leukemia development, likely because of a combination of decreased spontaneous apoptosis and enhanced immune suppression rather than increased proliferation. In addition, BRAF VE leukemia cells produced greater T-cell effects than Figure 6.…”
mentioning
confidence: 82%
“…Considering these data, the authors speculated that T-cell exhaustion is not irreversible in CLL. 43 Gassner et al also reported that euTCL1-derived T cells exhibited exhaustion.…”
Section: Lessons From Preclinical Cll Modelsmentioning
confidence: 95%
“…Examining the CLL T-cell compartment has resulted in novel mechanisms for CLL progression and interest in immunotherapeutic strategies. [41][42][43] To study the dependence of CLL B cells on immune subsets, carboxyfluorescein succinimidyl ester-labeled human CLL cells were injected into NSG mice alongside various immune components, such as CD34 1 progenitor cells, mesenchymal stromal cells, or mature APCs. 44 Data demonstrated that T cells activated by allogeneic APCs were required for leukemic cell survival and proliferation.…”
Section: Lessons From Preclinical Cll Modelsmentioning
confidence: 99%